Cloning and characterization of trehalase: a conserved glycosidase from oriental midge, Chironomus ramosus - Shukla, Ekta; Thorat, Leena; Bendre, Ameya D.; Jadhav, Santosh; Pal, Jayanta K.; Nath, Bimalendu B.; Gaikwad, Sushama M. (3 Biotech, 2018)
Insect trehalase is a multiferous enzyme, crucial for normal physiological functions as well as under stress conditions. In this report, we present a fundamental study of the trehalase gene segment (1587 bp) from Chironomus ramosus (CrTre) encoding for 529 amino acids, using appropriate bioinformatics tools. C. ramosus, a tropical midge is an emerging animal model to investigate the consequences of environmental stresses. We observed that CrTre belongs to GH family 37 in the CAZy database and possess 57-92% identity to dipteran trehalases. In silico characterization provided information regarding the structural, functional and evolutionary aspects of midge trehalase. In the phylogenetic tree, CrTre clustered with the soluble dipteran trehalases. Moreover, domain functional characterization of the deduced protein sequence by InterProScan (IPR001661), ProSite (PS00927 and PS00928) and Pfam (PF01204) indicated presence of highly conserved signature motifs which are important for the identification of trehalase superfamily. Furthermore, the instability index of CrTre was predicted to be < 40 suggesting its in vivo stability while, the high aliphatic index indicated towards its thermal stability (index value 71-81). The modelled 3D tertiary structure of CrTre depicts a (alpha/alpha)(6) barrel toroidal core. The catalytic domain of the enzyme comprised Glu424 and Asp226 as the putative active site residues. Interestingly, the conserved motifs were observed to be formed by the flexible loopy regions in the tertiary structure. This study revealed essential sequence features of the midge trehalase and offers better insights into the structural aspects of this enzyme which can be correlated with its function.
Keywords: Conserved motifs; Homology modelling; Midges; Secondary structure; trehalose